5x+2(1-x)=2(2x-4)

Simple and best practice solution for 5x+2(1-x)=2(2x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+2(1-x)=2(2x-4) equation:


Simplifying
5x + 2(1 + -1x) = 2(2x + -4)
5x + (1 * 2 + -1x * 2) = 2(2x + -4)
5x + (2 + -2x) = 2(2x + -4)

Reorder the terms:
2 + 5x + -2x = 2(2x + -4)

Combine like terms: 5x + -2x = 3x
2 + 3x = 2(2x + -4)

Reorder the terms:
2 + 3x = 2(-4 + 2x)
2 + 3x = (-4 * 2 + 2x * 2)
2 + 3x = (-8 + 4x)

Solving
2 + 3x = -8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
2 + 3x + -4x = -8 + 4x + -4x

Combine like terms: 3x + -4x = -1x
2 + -1x = -8 + 4x + -4x

Combine like terms: 4x + -4x = 0
2 + -1x = -8 + 0
2 + -1x = -8

Add '-2' to each side of the equation.
2 + -2 + -1x = -8 + -2

Combine like terms: 2 + -2 = 0
0 + -1x = -8 + -2
-1x = -8 + -2

Combine like terms: -8 + -2 = -10
-1x = -10

Divide each side by '-1'.
x = 10

Simplifying
x = 10

See similar equations:

| 6y-(y-2)=12/0.064/3 | | 9+v=-5 | | 4p^2-(2p^2-3p+1)= | | 11x-4=10x+5-6 | | x-5/8/2x-10/56 | | 3(x+4)-2(3x-5)+4x-1=4(2x-1)-(2x+5) | | 2x^2=7200 | | 79.49=100/6x | | -7x-27=8-1(1x-19) | | X/9=14/18 | | q^7-9q^5=0 | | ab-4a-4b+8=0 | | 5a+(-7)=-2 | | 4k-7+16=-3 | | 5x+20=24-3x-12 | | 7/(9-5i) | | 2x-4=3(-8-4x) | | 8-3x-(2x-4)=-3 | | (x^2y^3)/xy^4 | | 11/21*42 | | 3x-14y-7x-8y= | | 5910=(13790)r(5) | | (x/3)^2=729 | | a^4+49a^2=0 | | 9(x^2)-45x+56=0 | | 2w^2+11w-70=0 | | -2a(a-2b+5)= | | x/3^2=729 | | 2a=2b+4 | | 6=9+n | | 12x-46=-28+5x | | 3x/3=15/4 |

Equations solver categories